(3JSejW GdHQOIs - (3eMeO QVG Hf CMeO Hf MSf GdMdi GdeYQha HGdfMhis; (3CHh GdeYGdj eTQa Hf eQLj Hf EHQGgje GdebOSj, GHf eQLjs
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ Edi QHg GdZfi , eMeO GdedbH HGdQVG GHf GdTjN CMeO GdfMhi Efi deG hbaJ Ydi GdbUjOI GdHOjYjI GdZQGA GdehSheI HGdHQOI ddTjN TQa GdOjf CHj YHO Gddg eMeO Hf SYjO GdOdGUi GdeUQi GdHhUjQi s
(3BNQgG (B:s
(3hQfM Gdchf ef CeOGMge WQHG eGQfMJ YPHGJ GdHGf QjM GdUHG hCWQH GdYjSi MGOi GdYjS HGdfZe hGdMeO ddg QH GdYGdejf , hGdUdGI hGdSdGe Ydi NjQ Ndbg eMeO hYdi Bdg hUMHg CLejYf Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3GfXQg eY GdQSGdI GdMGJejI ai JNGejS GdHQOIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JSejW TYQis
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs